Mechanisms for improving the level of qualification and skills of teachers-psychologists (Gumilyov Journal of Pedagogy, 2025)
The article presents a structural and substantive model for improving the professional activity of a teacher-psychologist in general education institutions. The study examines the application of this model to schools in Astana, structured in seven blocks. In the studies, the first block of the model was used to theoretically determine the improvement of professional activity of teachers-psychologists in general education schools and to develop a model of it with the definition of pedagogical conditions. The problem of studying mechanisms that strengthen the desire of teachers-psychologists to improve the level of skills and abilities is relevant and important. The professional and pedagogical activity of a teacher-psychologist of an educational institution is the initial basis in relation to other types of activity, and knowledge and understanding of the motivational sphere of any specialist allows them to develop their professional self-awareness. At the stage of choosing a profession and in the process of its improvement as a professional, in the process of professionalization of a teacher-psychologist, changes occur that lead to the improvement of skills in their motivational sphere. Therefore, the problem of improving the professional and pedagogical activity of a school teacher-psychologist has a very important theoretical and practical significance, since the analysis of its various aspects increases the effectiveness of the educational system. A comparative analysis of the levels of formation of the integral criterion of professional competence in the studied schools showed that the indicators in both groups of respondents are at the same level.